HIV self‐testing intervention experiences and kit usability: results from a qualitative study among men who have sex with men in the SELPHI (Self‐Testing Public Health Intervention) randomized controlled trial in England and Wales. Issue 3 (10th December 2019) - Witzel, TC; Bourne, A; Burns, FM; Rodger, AJ; McCabe, L; Gabriel, MM; Gafos, M; Ward, D; Collaco‐Moraes, Y; Dunn, DT; Speakman, A; Bonell, C; et al.
Abstract : Objectives: SELPHI (HIV Self‐Testing Public Health Intervention) is the largest randomized controlled trial (RCT) of HIV self‐testing (HIVST) in a high‐income setting to date, and has recruited 10 000 men who have sex with men (cis‐ and transgender) and transgender women who have sex with men. This qualitative substudy aimed to explore how those utilizing self‐tests experience HIVST and the implications for further intervention development and scale‐up. This is the first qualitative study in Europe investigating experiences of HIVST among intervention users, and the first globally examining the experience of using blood‐based HIVST. Methods: Thirty‐seven cisgender MSM SELPHI participants from across England and Wales were purposively recruited to the substudy, in which semi‐structured interviews were used to explore testing history, HIVST experiences and intervention preferences. Interviews were audio‐recorded, transcribed and analysed through a framework analysis. Results: Men accessed the intervention because HIVST reduced barriers related to convenience, stigma and privacy concerns. Emotional responses had direct links to acceptability. Supportive intervention components increased engagement with testing and addressed supportive concerns. HIVST facilitated more frequent testing, with the potential to reduce sexually transmitted infection (STI) screening frequency. Substudy participants with an HIV‐positive result ( n  = 2) linked to care promptly and reported very high acceptability. Minor adverse outcomes ( n  = 2; relationship discord and fainting) did not reduce acceptability. Ease of use difficulties were with the lancet and the test processing stage. Conclusions: Intervention components shaped acceptability, particularly in relation to overcoming a perceived lack of support. The intervention was broadly acceptable and usable; participants expressed an unexpected degree of enthusiasm for HIVST, including those with HIV‐positive results and individuals with minor adverse outcomes.